The Relationship between Arm Muscle Strength and Tosser Athletes in State High School Volleyball 13 Muko-Muko - Deliah Ahmad (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the scientific relationship between arm muscle strength and upper passing skills (Tosser) in volleyball. The formulation of the problem in this research is how big is the relationship between arm muscle strength and passing skills in volleyball games at SMA Negeri 13 Muko-Muko? This research was conducted at the Volleyball Development Club of SMA Negeri 13 Muko-Muko. The research method used is the correlation method with product moment statistics, this research is objective or what it is with a sample of 30 athletes assisted by the Volleyball Club of SMA Negeri 13 Muko-Muko taken with a total sampling technique. The results of the data Based on the results of research conducted at the Volleyball Club of SMA Negeri 13 Muko-Muko using the data normality test, homogeneity test, hypothesis testing, it can be concluded as follows: 1) Test results and measurement of arm muscle strength through push up tests on skills passing over a volleyball game is normally distributed, 2) Based on the results of tests that have been carried out that arm muscle strength has a significant relationship with passing skills in volleyball games